A PIRÓLISE COMO PROCEDIMENTO DE CONVERSÃO TÉRMICA NA VALORIZAÇÃO ECONÔMICA DOS RESÍDUOS DA ERVA-MATE (ILEX PARAGUARIENSIS) ORIUNDOS DA BEBIDA TERERÉ: ESTUDO DA COMPOSIÇÃO QUÍMICA DO BIO-ÓLEO E DAS CARACTERÍSTICAS DO BIOCARVÃO - Érico Vinícius Rocha Sanches (2021)
The depletion of oil reserves and the environmental issues involved in the use of fossil fuels have generated interest in the use of biomass for the source of renewable sources and chemicals with high added value. Currently, the most common process of valorization of biomass consists of its thermochemical conversion, with emphasis on the pyrolysis process. A study on the thermal conversion of yerba mate residues (REM) resulting from the consumption of tereré drink, specific to the production and characterization of bio-oil and biochar, is presented here. Yerba mate (Ilex paraguariensis) is a plant native to South America and extends to Brazil, Argentina and Paraguay. It is estimated that in the state of Mato Grosso do Sul, the average annual consumption per capita is 1.45 kg, which demonstrates an expressive production of waste that can be used as a source of biomass. For the pyrolysis process, a system consisting of a muffle oven and borosilicate glasstiles adapted. Analyzes of TG/DTG curves, which indicated the presence of macromolecules characteristic of lignocellulosic biomass for REM. Three different pyrolysis final temperatures (450, 550 and 650 ° C) were evaluated. Higher yield of liquid products was obtained, [58.8% (m / m)] with heat treatment of 650 ° C, indicating that the increase in the final temperature of pyrolysis favors the formation of liquid products. To study the chemical composition of bio-oil, a gas chromatograph hyphenated with a mass spectrometer. In the highest yield condition, 29 compounds were identified in the aqueous fraction and 84 compounds in the organic fraction. The highest chemical class, in terms of percentage of relative area, for both fractions was phenols (50.16% in the aqueous phase and 27.17% in the organic phase). In addition to phenols, other major groups were detected in the organic phase, such as esters and aromatic hydrocarbons (7.00% and 7.07%), while in the aqueous phase the second major group was nitrogen compounds (18.55%). Syringol, 3-methoxy-catechol and catechol were the major substances in aqueous fractions. In the organic fraction, the major substances are m-cresol, phenol and syringol, followed by saturated and aromatic hydrocarbons. The results obtained show that REM is a promising biomass in the production of bio-oil, thus adding economic value to this residue. With regard to biochar, the analyzes giving TG/DTG curves indicated that the increase in temperature favored products with a high fixed carbon content (82.84%) confirmed by the EDX analyzes, which presented values close to 89.90% for the biochar produced at 650 ° C. The O / C atomic ratio for this biochar was 0.05 indicating the presence of stable aromatic structures. The SEM micrographs of the samples indicated the presence of a porous surface, which favors the adsorption process. XRD analyzes were characteristic of amorphous material. Adsorption isotherms using the methylene blue dye were adjusted to the mathematical models of Langmuir, Freundilich and Temkin, and the Freundlich model was the one that most adjusted to the biocarbons produced, suggesting the adsorption in multilayers. The maximum adsorption capacity (38.551 mg g-1) was observed for biochar produced at a temperature of 650 ° C, suggesting the biochar produced through the REM as suitable for the adsorption of the methylene blue dye in aqueous solution.